Relevance of School Plant Availability and Functionality on Students’ Academic Performance in Senior Secondary Schools in Rimi Zonal Education Quality Assurance, Katsina State - Muhammad, , T. (Kashere Journal of Education, 2021)
The study explored the relevance of school plant availability and functionality on students’ academic performance in Senior Secondary Schools in Rimi Zonal Education Quality Assurance, Katsina State. Two research questions were formulated to guide the study. Exploratory survey design is employed for the study. The study has a population of 406 teachers and a sample size of 196 teachers using Research Advisors (2006). Two null hypotheses were formulated and tested using Pearson correlation analysis for independent samples. Questionnaires were used as the instrument for data collection; the instrument was given to the senior lecturers’ department of educational management Umar Musa Yar’adua University, Katsina to ascertain its validity, from the copies returned by the lecturers, corrections were made by the researcher to ensure the instrument has both good content and construct validity. Pilot test was conducted to establish the reliability of the instrument and result showed that the instrument has a very high level of reliability index of 0.84, which the researcher considered adequate for the study. Findings showed that school plant availability and functionality have significant influence on academic performance among Senior Secondary School students in Rimi Zonal Education Quality Assurance. The study recommended among others that School based management committees should be involved in the provision of school plant and ensuring that the plants are always functional in their respective schools through periodic maintenance; as the world nowadays is technologically advanced, modern educational resources such as internet, Information and communications technology facilities should be provided by stakeholders and teachers should be trained on how to effectively use such facilities for effective teaching and learning process in secondary schools.